Experience in cultivating Scots pine seedlings using plant growth regulators in the Klavdiyevske Forestry Enterprise - Yashchuk, I. V.; Shlonchak, G. A. (Forestry and Forest Melioration, 2019)
Introduction The main way to produce forest trees seedlings is to grow them in a seedling nursery. Recently, many forest state enterprises have been growing seedlings in the boxes due to the deficiency of organic manure and absence of irrigation in forest seedling nurseries. For that reason, the usage of the effective nontoxic and ecological plant growth regulators that bring about higher efficiency in forest-species seedlings producing is an urgent matter. Materials and Methods We used the 3-class-quality seeds to grow the Scots pine seedlings in the boxes in the Klavdiyevske Forest Enterprise. Before sowing, the seeds were treated by solutions of the Emistym C and Ivin plant growth regulators of various concentrations. The exposure time was 18 hours for all variants. There were such treatment variants as Emistym C – 0.1ml/l, 0.01ml/l, 0.001ml/l and Ivin – 0.1ml/l, 0.01ml/l, 0.001 ml/l. The control sampling was treated by water. After treatment the seeds were sown into the boxes. The seedlings were growing in the environmental conditions. The sowing area was irrigated by an automatic irrigation system on a daily basis. The quantity of water was 3 l/m2. The boxes were covered by a net. The seedlings were sprayed by the ‘Previcure’ fungicide to protect them from fungus during the whole vegetation period. The germination, survival rate, biometric and weight indices were studied during the vegetation period and at the end of it. Results During the vegetation period after the seeds germinated, we studied their germination ability. In all treatment variants it was higher than in control. The highest germination was observed in the Emistym 0.1ml/l variant namely 77%, that is 118% compared to control. Furthermore, we determined the survival rate and quantity of the standard seedlings at the end of the vegetation period. The survival rate was 85.6%, which is 110.6% compared to control. The experimental seedlings had higher biometric indices in comparison to control ones. The best weight indices were in the Emistym 0.1ml/l treatment variant. Conclusions The treating Scots pine seeds with plant growth regulators is an effective way to enhance their germination. Usage of the plant growth regulators had also a positive influence on the biometric and weight indices of the experimental seedlings. The best treatment variant was Emistym 0.1ml/l. 3 Tables, 2 Refs.